2015
DOI: 10.1590/1809-4430-eng.agric.v35n4p646-656/2015
|View full text |Cite
|
Sign up to set email alerts
|

Características comportamentais de suínos em crescimento e terminação em sistema “wean to finish”

Abstract: RESUMO:O "wean to finish" é um sistema de criação de suínos, no qual os animais permanecem em uma mesma instalação do desmame até à fase de abate. Objetivou-se estudar o comportamento dos animais em alojamento exclusivo de 26 machos suínos (T1), misto (T2), contendo 13 machos e 13 fêmeas, e o tratamento único de fêmeas (T3), com 26 animais. Para isso, utilizou-se da análise multivariada, por meio da análise dos gráficos de componentes principais, por ser um artifício interessante utilizado por diversos pesquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Digging behavior is strongly related to eating behavior; it was observed by Massari et al (2015) that domestic pigs exploit the environment in search of food. However, Stevenson (2000) found that under natural breeding conditions, pigs spent about 75% of their time in activities such as digging, searching for food and exploring the environment; confinement in highly stocked bins without environmental enrichment makes it impossible to perform these behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Digging behavior is strongly related to eating behavior; it was observed by Massari et al (2015) that domestic pigs exploit the environment in search of food. However, Stevenson (2000) found that under natural breeding conditions, pigs spent about 75% of their time in activities such as digging, searching for food and exploring the environment; confinement in highly stocked bins without environmental enrichment makes it impossible to perform these behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that if different time intervals were used in behavioral sampling, this would result in different behavioral frequencies for the focal behaviors from those measured during continuous observation. Massari et al (2015) employed the focal animal methodology previously proposed by Altmann (1974) with 15 min of observation and 3-min intervals to assess typical behaviors (standing, lying, and eating) and continuous observation for dynamic behaviors (social interaction and agonistic, exploratory, and stereotypic behaviors) to compare the behavior of pigs in the grower and finisher phases using the "wean to finish" system. That methodology suggests that intervals and observation period must be determined according to the characteristics of each behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency of visits and the act of projecting the head toward the drinking fountain, triggering the system without drinking water properly (drinker-playing) (Chen et al, 2020), as seen in the bed systems, especially in pens with wood shavings substrate, can be interpreted as stereotypies or obsessive behavior (Maia et al, 2013;Massari et al, 2015).…”
Section: Behaviormentioning
confidence: 99%
“…Piglets may exhibit changes in their behavior patterns depending on the environment in which they are kept. Massari et al (2015) state that "eating" behavior has an inverse relationship with air temperature and a strongly positive relationship with exploratory behaviors and agonistic interactions, since exploratory behaviors are often related to the search for food.…”
Section: Behaviormentioning
confidence: 99%
See 1 more Smart Citation